Control of diffusion and exudation of vegetable oils in EPDM copolymers. (September 2016) - Bétron, Cyrille; Cassagnau, Philippe; Bounor-Legaré, Véronique
Graphical abstract: The plastification of EPDM was carried out using modified vegetable oils and a very reactive tung oil. Obtained results showed that the standoil reaction lead to a large decrease of the exudation from 8 wt% to less than 1 wt% with the in situ polymerisation. Thus this encouraging result was similar to the one obtained when the EPDM polymer was plasticised with a mineral oil. Structure of the tung oil and variation of the torque and temperature versus mixing time for the EPDM/tung oil (70/30 wt%). Highlights: Diffusion of vegetable oils and commercial oil bio based in EPDM matrix. Standoil curing of tung oil. Thermal curing of EPDM and tung oil blend for prevent the exudation. Abstract: As a response to environmental problems caused by plasticisers, the feasibility of replacing a significant proportion of the plasticisers in a synthetic ethylene-propylene-diene monomer copolymer (EPDM) matrix with bio-based materials was studied. In that context, different bio-based commercials plasticisers such as Radia® supplied by Oleon, methyl ester of soybean oil, epoxidized methyl ester of soybean oil, methyl oleate, methyl linoleate and untreated vegetable oils (rapeseed, soybean, linseed and tung) were tested. Diffusion analysis using the bi-layers rheology method and exudation analysis highlighted an important exudation phenomenon at 80 °C for all oils tested. To overcome this problem, a second part of this work was focused on the use of a specific highly reactive vegetable tung oil. The in situ polymerisation of this oil by thermal activation without the use of catalysts allowed to totally prevent the exudation phenomenon by increasing the viscosity of the oil. Compared with the use of pure tung oil, the degree of exudation was greatly decreased, from more than 8% to less than 1%.